Experiences of Austrian mothers with mobility or sensory impairments during pregnancy, childbirth and the puerperium: a qualitative study - Schildberger, Barbara (BMC Pregnancy Childbirth, 2017)
BACKGROUND: Approximately 8% of all women of childbearing age in Austria live with permanent impairments. In everyday life, women with disabilities face various challenges and discrimination, among which the issue of pregnancy and motherhood, in particular, is often considered taboo, and their parenting abilities are doubted. Knowledge in the medical field about the experiences of women with disabilities during pregnancy, childbirth and the puerperium is limited. METHODS: To investigate the personal meanings and experiences of women with disabilities in regard to pregnancy, childbirth and the puerperium, in-depth individual, semi-structured interviews were conducted with ten mothers with various mobility or sensory impairments who reside in Austria. The qualitative interview data were analyzed using the qualitative content analysis proposed by Mayring. RESULTS: Three main themes or categories emerged from the inductive content analysis, namely, (i) the social network, (ii) self-efficacy and self-awareness and (iii) communication, transparency and information. Participants reported limited acceptance of their life decisions and experienced an environment of discriminatory attitudes. They experienced a lack of support and lack of confidence in their parenting abilities, which negatively influenced their self-efficacy and self-awareness. Violations of personal borders and a feeling of being watched and controlled were reported. Communication with health care professionals was often characterized by mutual aspects of fear, uncertainty and awkwardness, as perceived by women with disabilities. Adequate information about pregnancy, childbirth and the puerperium, particularly about measures taken and interventions applied, was frequently missing. CONCLUSION: Heath care facilities need to be structured to ensure ease of access for women with disabilities. Education should be offered to health care professionals to improve knowledge about care for women with disabilities and to strengthen communication skills. All necessary information needs to be prepared and provided in an adequate manner. The establishment of a health-promoting environment for mothers, their children and their families requires a sensitive, respectful and non-judgmental attitude of society toward women with disabilities during pregnancy, childbirth and the puerperium. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-017-1388-3) contains supplementary material, which is available to authorized users.